Open Peer Reviewers in Africa Workshop Trainer Guide - Munene, Aurelia; Onwuchekwa, Godwyns; Alsop, Shane; Ngugi, Joyce Wangari; Owango, Joy; Havemann, Johanna; Saderi, Daniela (My University, 2022)
This Trainer Guide is meant to help researchers and professionals who want to be Trainers for the Open Peer Reviewers in Africa workshop series. In order to be a Trainer, we recommend that you have attended the workshop yourself as a cohort trainee. Our goal is to establish a Trainer-of-Trainers (ToT) model in which workshop participants are encouraged and empowered to mobilize, recruit and train colleagues in their respective scholarly communities. This guide is NOT meant to be prescriptive about how anyone should conduct their training. We encourage you to consider the content as suggestions for your own training and feel free to adapt it to your needs and circumstances.
Keywords: Training; Mentorship; Peer Review